ANALISIS KEMAMPUAN SISWA KELAS XI DALAM MENYELESAIKAN SOAL LITERASI NUMERASI MATERI TURUNAN - Myrela, Angel Ceria; Khuzaini, Nanang (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
Numeracy literacy entails the knowledge and skills to utilize various numbers and symbols associated with basic mathematics to solve problems in everyday life and analyze information presented in different symbols, subsequently using the results of this analysis to make decisions. In 2018, based on the PISA results released by the OECD, Indonesia's numeracy literacy level was ranked 74th out of 79 countries, indicating that Indonesia's numeracy literacy level is still very low. This study aims to determine and describe the numeracy literacy skills of eleventh-grade students in solving numeracy literacy problems on derivative material at SMA N 1 Sedayu in the academic year 2023/2024. The subjects in this study were 22 eleventh-grade students. The method used in this research is descriptive qualitative. Data collection techniques used were numeracy literacy ability tests and interviews. The numeracy literacy indicator in this research consists of 3 components, namely: (1) identifying and explaining mathematical concepts; (2) designing and applying mathematical concepts; (3) interpreting calculation results. The instrument in this research consists of 3 items of Numeracy Literacy material on Derivatives. The research results showed that 77% of students were in the low category, 14% of students were in the medium category, and 9% were in the high category, thus it can be concluded that in general, students' ability to solve numeracy literacy problems is still low.